COGNITIVE RESTRUCTURING TECHNIQUES FOR CONTROLLING THE SELF-CONTROL OF VICTIMS OF DRUGS ABUSE - Bela Janare Putra; Lena Marianti; Hartika Utami Fitri; Rikas Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to determine the description of the discretion of victims of drug addiction before implementing group counseling services with cognitive restructuring techniques, to determine the impact of group counseling with cognitive restructuring techniques on self-control of drug abuse victims and to find out the description of self-control after being given group counseling services using this technique. cognitive restructuring. The research in this study used a quantitative approach with experimental research methods. The subjects in this study were 10 adult victims of drug abuse in village X, OKU Timur district. Data collection techniques using questionnaires, interviews and documentation. The data analysis technique used the t-test pared t-test. The results of this study indicate that the effect of self-control on victims of drug abuse after group counseling with cognitive restructuring techniques is categorized as moderate because the average value is 6.72 and after the average value is 8.25. So, it can be concluded that group counseling using cognitive restructuring techniques is effective in increasing self-control for victims of drug abuse, which can be seen from the results and data that rcount t table = 0.05, which is 7.504 two.10092 so that Ho is rejected and Hα is accepted.Keywords : Cognitive restructuring techniques, self control, drugs.